The Effect and Mechanism of Cultural Capital on Chinese Residents’ Participation in Physical Activities - Ren, Huitao; Liu, Wei (Frontiers in Psychology, 2022)
Background Using Bourdieu’s cultural capital theory, this paper discusses the inequality of Chinese urban residents’ participation in physical activities caused by cultural capital and explores the relationship and role of residents’ income and self-rated health in cultural capital and physical activity participation. Methods Using Chinese social survey data (2017), the proposed assumptions were tested and analyzed by using a linear regression model. Results Cultural capital can promote the participation of Chinese urban residents in physical activities, and personal income and health self-assessment play an intermediary role in promoting residents’ participation in physical activities. Conclusion Promoting Chinese residents’ participation in physical activities can be realized not only through traditional publicity and sports venue construction but also by increasing residents’ educational level, art appreciation level and health awareness.